Evolution of I-SceI homing endonucleases with increased DNA recognition site specificity - Joshi, Rakesh (2010)
Elucidating how homing endonucleases undergo changes in recognition site specificity will facilitate efforts to engineer proteins for gene therapy applications. I-SceI is a monomeric homing endonuclease that recognizes and cleaves within an 18-base-pair (bp) target. It tolerates limited degeneracy in its target sequence, including substitution of a C/G(+4) base-pair for the wild-type A/T(+4) base-pair. Libraries encoding randomized amino acids at I-SceI residue positions that contact or are proximal to A/T(+4) were used in conjunction with a bacterial one-hybrid system to select I-SceI derivatives that bind to recognition sites containing either the A/T(+4) or C/G(+4) base-pairs. As expected, isolates encoding wild-type residues at the randomized positions were selected using either target sequence. All I-SceI proteins isolated using the C/G(+4) recognition site included small side chain substitutions at G100, and either contained (K86R/G100T, K86R/G100S and K86R/G100C) or lacked (G100A, G100T) a K86R substitution. Interestingly, the binding affinities of the selected variants for the wild-type A/T(+4) target are 4–11-fold lower than that of wild-type I-SceI, whereas those for the C/G(+4) target are similar. The increased specificity of the mutant proteins is also evident in binding experiments in vivo. These differences in binding affinities account for the observed ~36-fold difference in target preference between the K86R/G100T and wild-type proteins in DNA cleavage assays. An X-ray crystal structure of the K86R/G100T mutant protein bound to a DNA duplex containing the C/G(+4) substitution suggests how sequence specificity of a homing enzyme can increase. This biochemical and structural analysis defines one pathway by which site specificity is augmented for a homing endonuclease.